Unobserved Worker Quality and Inter-Industry Wage Differentials - Suqin Ge; Jo\~ao Macieira (Global Labor Organization (GLO), 2020)
This study quantitatively assesses two alternative explanations for inter-industry wage differentials: worker heterogeneity in the formof unobserved quality and firmheterogeneity in the form of a firm's willingness to pay (WTP) for workers' productive attributes. We develop an empirical hedonic model of labor demand and apply a two-stage nonparametric procedure to recover worker and firm heterogeneities. In the first stage we recover unmeasured worker quality by estimating market-specific hedonic wage functions nonparametrically. In the second stage we infer each firm's WTP parameters for worker attributes by using first-order conditions from the demand model. We apply our approach to quantify inter-industry wage differentials on the basis of individual data from the NLSY79 and find that worker quality accounts for approximately two thirds of the inter-industry wage differentials.
Keywords: J31; J24; C51; M51; 330; hedonic models; inter-industry wage dierentials; labor quality; wage determination